Dimensions of the Industry 4.0 Implementation In Manufacturing Industry: Literature Review - Anna MICHNA; Joanna KRUSZEWSKA (Communications of International Proceedings, 2022)
Digital transformation, digitalization, Industry 4.0 solutions implementation, changes in business models - all those became a requirement for organizations due to recent world situation – lack of resources, broken logistic chains, higher competitiveness and excessive costs. Step by step, fourth industrial revolution influences more and more companies. The aim of this article is to present a summary of performed literature review in the area of dimensions of Industry 4.0 solutions implementation. Further deliberations of that publication are connected with an attempt to group dimensions provided by study literature according to the processes taking place in production companies – functional areas. As a practical aspect of the presented research, all models and outcomes will be used for next planned empirical study in the Polish automotive market. The information in this paper may be of used to summarize information regarding maturity assessment or readiness model for Industry 4.0 implementation.
Keywords: Industry 4.0; Maturity Model; Readiness Model; Small Medium Enterprise (SME); Sustainability